Epilithic Microbial Community Functionality in Deep Oligotrophic Continental Bedrock - Nuppunen-Puputti, Maija; Kietäväinen, Riikka; Raulio, Mari; Soro, Aino; Purkamo, Lotta; Kukkonen, Ilmo; Bomberg, Malin (Frontiers in Microbiology, 2022)
The deep terrestrial biosphere hosts vast sessile rock surface communities and biofilms, but thus far mostly planktic communities have been studied. We enriched deep subsurface microbial communities on mica schist in microcosms containing bedrock groundwater from the depth of 500 m from Outokumpu, Finland. The biofilms were visualized using scanning electron microscopy, revealing numerous different microbial cell morphologies and attachment strategies on the mica schist surface, e.g., bacteria with outer membrane vesicle-like structures, hair-like extracellular extensions, and long tubular cell structures expanding over hundreds of micrometers over mica schist surfaces. Bacterial communities were analyzed with amplicon sequencing showing that Pseudomonas, Desulfosporosinus, Hydrogenophaga and Brevundimonas genera dominated communities after 8–40 months of incubation. A total of 21 metagenome assembled genomes from sessile rock surface metagenomes identified genes involved in biofilm formation, as well as a wide variety of metabolic traits indicating a high degree of environmental adaptivity to oligotrophic environment and potential for shifting between multiple energy or carbon sources. In addition, we detected ubiquitous organic carbon oxidation and capacity for arsenate and selenate reduction within our rocky MAGs. Our results agree with the previously suggested interaction between the deep subsurface microbial communities and the rock surfaces, and that this interaction could be crucial for sustaining life in the harsh anoxic and oligotrophic deep subsurface of crystalline bedrock environment.